Larangan Tidur Bersama Sebelum Selesainya Resepsi Pernikahan di Desa Tanjung Damai Kec. Siak Kecil Kab. Bengkalis - Dwi Aryani Chairunnisa; Milhan Milhan (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
This article discusses the tradition in Tanjung Damai Village regarding the prohibition of sleeping together before the wedding reception is finished. This tradition originates from Javanese people who transmigrated to Tanjung Damai Village. The reason society forbids married brides and grooms from having husband and wife relations before the wedding reception is finished is because it is feared that the bride will not give off a beautiful aura at the wedding and can cause fatigue during the wedding reception such as fainting. This research uses a qualitative descriptive method with the type of field research. The data source in this research is direct information from informants using a semi-structured interview system. In data analysis techniques, researchers collect data which is then reduced, presented and then concluded. This tradition is contrary to Islamic law because when the marriage contract has been pronounced, it has become lawful for them and they are allowed to sleep together like husband and wife.